INTEGRATION OF DATA FROM HETEROGENEOUS SOURCES USING ETL TECHNOLOGY. - Macura, Marek (Computer Science, 2014)
Data integration is a crucial issue in environments of heterogeneous data sources. At present mentioned heterogeneity is becoming widespread. Whenever, based on various data sources, we want to gain useful information and knowledge we must solve data integration problem in order to apply appropriate analytical methods on comprehensive and uniform data. Such activity is known as knowledge discovery from data process. Therefore approaches to data integration problem are very interesting and bring us closer to the "age of information". The paper presents an architecture, which implements knowledge discovery from data process. The solution combines ETL technology and wrapper layer known from mediated systems. It also provides semantic integration through connections mechanism between data elements. The solution allows for integration of any data sources and implementation of analytical methods in one environment. The proposed environment is verified by applying it to data sources on the foundry industry.